Analisis Pembelajaran Nahwu pada Siswa Kelas 2 Ula Madrasah Diniyah Salafiyah Islamiyah Tanggulangin Sidoarjo - Rohman, Muhammad Arifur; Anwar, Najih (Indonesian Journal Publisher, 2024)
Nahwu is a science that studies the rules that can be used to find out the law of the final state of an Arabic word. Nahwu learning is very important in Islamic boarding schools and madrasas. This study aims to: 1. determine nahwu learning for students. 2. knowing the difficulties of learning nahwu experienced by students. 3. know the solution to overcome the difficulties in learning nahwu students. This type of research is a qualitative research with a descriptive approach. The subjects in this study were the principal, nahwu teachers, and grade 2 ula students. Data was collected by observation, interviews, and documentation. While in data analysis, namely data reduction, data presentation and conclusion drawing. The results showed that: 1. Class 2 Ula nahwu learning activities included lesson planning, learning implementation, and learning evaluation. 2. Difficulties in learning nahwu experienced by students occur due to several factors, including: a. Students' interest in learning nahwu is low. b. Students assume that learning nahwu is difficult. c. Students do not want to pay close attention to nahwu learning. 3. The solutions offered to overcome these problems include: a. Cultivate students' interest in learning nahwu. b. Convincing students that learning nahwu is not difficult and complicated. c. Using methods and media that are preferred by students.